Internal consistency of the self-reporting questionnaire-20 in occupational groups - Kionna Oliveira Bernardes Santos; Fernando Martins Carvalho; Tânia Maria de Araújo (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To assess the internal consistency of the measurements of the Self-Reporting Questionnaire (SRQ-20) in different occupational groups. METHODS A validation study was conducted with data from four surveys with groups of workers, using similar methods. A total of 9,959 workers were studied. In all surveys, the common mental disorders were assessed via SRQ-20. The internal consistency considered the items belonging to dimensions extracted by tetrachoric factor analysis for each study. Item homogeneity assessment compared estimates of Cronbach's alpha (KD-20), the alpha applied to a tetrachoric correlation matrix and stratified Cronbach's alpha. RESULTS The SRQ-20 dimensions showed adequate values, considering the reference parameters. The internal consistency of the instrument items, assessed by stratified Cronbach's alpha, was high (> 0.80) in the four studies. CONCLUSIONS The SRQ-20 showed good internal consistency in the professional categories evaluated. However, there is still a need for studies using alternative methods and additional information able to refine the accuracy of latent variable measurement instruments, as in the case of common mental disorders.